2015
DOI: 10.1111/ajag.12223
|View full text |Cite
|
Sign up to set email alerts
|

Bystander attitudes toward parents? The perceived meaning of filial piety among Koreans in Australia, New Zealand and Korea

Abstract: The results show that the tension between the social and economic aspects of filial piety often creates a 'bystander' attitude toward parents and provides fertile ground for the seeds of family conflict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The accounts in this study help explain why it is difficult to pin down the extent that filial piety serves as an academic motivator because of the complex human factors that reductionist studies cannot adequately account for. This is especially the case for this study's sample where traditional collectivist values are being eroded in an age of globalization and migration (see also Park & Kim, 2015).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The accounts in this study help explain why it is difficult to pin down the extent that filial piety serves as an academic motivator because of the complex human factors that reductionist studies cannot adequately account for. This is especially the case for this study's sample where traditional collectivist values are being eroded in an age of globalization and migration (see also Park & Kim, 2015).…”
Section: Resultsmentioning
confidence: 91%
“…In Park and Kim's (2015) comparative study of Koreans in different geographical settings, filial piety norms of family care and support, along with respect for parents, were found to remain as the intergenerational norm for Koreans. However, they found that filial piety's practices erode with major sociocultural and economic changes, such as migration.…”
Section: Filial Piety In Confucian Heritage Culturesmentioning
confidence: 96%
“…These two aspects of filial principles are interrelated and are interwoven but, at the same time, meaningfully distinctive from each other relative to their roles and functions in different individuals and families. The discussion on the findings concerning filial piety between living generations has been discussed elsewhere (Park & Kim, 2016), and thus, this article focuses on presenting the practice of ancestor worship and anything related to it across living and past generations. For this focus, four themes on ancestral engagement are significantly evident: (1) moving from ancestor worship to memorial piety; (2) memorial practices practised by descendants; (3) scepticism on current memorial practices; and (4) a need to support future ancestors.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of these transforming circumstances, arguably the core principle of filial piety (including ancestor respect) remains in the public consciousness, and its impacts on people's daily lives are still meaningful in contemporary Korean society (Park & Kim, 2016;Sung, 2007). Notably, now Korean Christianity has chosen to promote filial piety as an indigenous way of achieving harmony between young and old, and gradually has accepted the practice of memorial service for ancestors (Park & Mu¨ller, 2014).…”
Section: Parkmentioning
confidence: 99%